Thermocoagulation in Multiple Targets to Treat Obsessive-Compulsive Disorder Associated with Drug Addiction: Case Report - Assis, Laryssa Simões de Lima; Carvalho, Laura Araújo de; Silva, Ledismar José da (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Substance-related disorders are chronic psychiatric conditions defined by substance abuse, and they compromise patients both clinically and functionally. Currently, pharmacotherapy, behavioral therapy, or an association of both are the treatments of choice for obsessive-compulsive disorder associated with drug addiction. However, the refractoriness to treatment, as a result of the high failure rates of these approaches, has led to the need to develop surgical techniques to treat severe cases of substance-related disorders. In the present article, we report the case of a patient who underwent neurosurgery through the stereotactic technique after refractoriness to the conventional treatment for drug addiction. The patient showed sustained improvement in his addiction to drugs. Despite the numerous reports on the effectiveness and applicability of neurosurgery in psychiatric disorders, some concerns regarding stereotactic surgery as a treatment for drug addiction still remain, especially in relation to its efficacy, safety, and ethical implications.
Keywords: obsessive compulsive disorder; drug addiction; thermocoagulation; case report